2007
DOI: 10.1016/j.trsl.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of acute graft-versus-host disease: recent advances

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) is a potentially curative therapy for many malignant and non-malignant hematological diseases. Donor T cells from the allografts are critical for the success of this effective therapy. Unfortunately these T cells not only recognize and attack the disease cells/tissues but also the other normal tissues of the recipient as 'foreign' or 'nonself' and cause severe immune mediated toxicity, Graft-versus-Host Disease (GVHD). Several insights into the complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
101
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 259 publications
0
101
0
3
Order By: Relevance
“…[43][44][45] Our results showed pathological alterations in skin and large intestine, but not the liver at day 0 which probably is because the liver is highly specialized to detoxify xenobiotics, and that the threshold of BU-CY induced toxicity in the liver is higher than that for skin, large intestine and lymphoid organs. Several studies have shown that donor T cells are activated by recipients/donor antigen-presenting cells in the secondary lymphoid organs such as the spleen, lymph nodes and Peyer's patches.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…[43][44][45] Our results showed pathological alterations in skin and large intestine, but not the liver at day 0 which probably is because the liver is highly specialized to detoxify xenobiotics, and that the threshold of BU-CY induced toxicity in the liver is higher than that for skin, large intestine and lymphoid organs. Several studies have shown that donor T cells are activated by recipients/donor antigen-presenting cells in the secondary lymphoid organs such as the spleen, lymph nodes and Peyer's patches.…”
Section: Discussionmentioning
confidence: 93%
“…However, in a 3-phase model proposed for the pathogenesis of aGVHD, [43][44][45] including phase 1, where the conditioning regimen leads to the initial damage and activation of dendritic cells of the host tissues which provides a condition for the migration and activation of donor T cells to the target organ tissue in phase-2. [43][44][45] The importance of donor T cells in target organ pathology has been shown earlier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GVHD involves an extremely complex pathophysiological process. It is currently believed that the activation and amplification of donor T lymphocytes as well as the release of a large number of inflammatory cytokines are the two main factors involved in the occurrence of acute GVHD (Sun et al, 2007;Reddy et al, 2009). CD 4 + T cells, especially Th cells, play an important role in the initiation and amplification of the severe GVHD pathological process.…”
Section: Discussionmentioning
confidence: 99%
“…11,39 An alternative approach relies on the infusion of specific cell types with immunoregulatory effects: clinical phase I-II trials have underlined the efficacy and safety of mesenchymal stem cells in combination with immunosuppressive drugs in the treatment of steroid-resistant GvHD, although subsequent studies, including phase III trials, failed in reproducing initial results. 40,41 Finally, after encouraging results from studies in murine models, [42][43][44] several groups are currently exploring the immunosuppressive activity of regulatory T cells, such as natural CD4+CD25+Foxp3+ and Tr1 lymphocytes, in preventing or controlling GvHD in clinical trials. 45 Suicide gene therapy is a novel promising application that exploits alloreactivity against malignant cells with a safe control of GvHD…”
Section: The Adoptive Transfer Of Selected Antigen-specific Lymphocytmentioning
confidence: 99%